A Review on Asura Graha Unmada with Contemporary View (International Journal of Ayurveda and Pharma Research, 2022)
Narcissistic Personality Disorder (NPD) causes problems in many areas of life, such as relationships, occupational field or financial affairs. Narcissistic personality disorder individual generally unhappy and disappointed. They believe they deserve admiration. According to Acharya Charak, Unnmad, is the Manasvyadhi is which understood as the disturbed condition of the Manas (mind), Buddhi (understanding), Samjna (consciousness), Gynana (perception), Smriti (memory), Bhakti (inclination), Sheela (character), Chesta (behaviour), and Achara (conduct). As a result, Citta gets disturbed and in turn causes impairment of Budhhi. Due to this, the individual person feels different sign and symptoms like loss of confidence, irrelevant talk, biased willing and thinking, deprived memory, decision and responsiveness. The signs and symptoms of Asura Graha Unmada (AG) such as Jihma Drishtim, Dushtaatmaanaam, Krodhanam, Atruptam, Sasweda Gaatram, Deva, Braahmana, Guru Dveshinam, etc show similarity with deceitfulness, exploitation, antisocial, aggressiveness, impulsivity, negative emotionality, grandiosity, dysphoria, alcohol abuse, and physical violence features commonly found in various personality disorders such as Anti-Social Personality Disorder (ASPD) , Bipolar Disorder (BD), and NPD and others personality disorder or comorbid condition among them. Manasa Vyadhi, Graha Rogas are less focused topic in Ayurveda. The aim of this article to explain Asura Graha Unmada and its correlation with contemporary view. After proper review it is concluded that the signs and symptoms of Asura Graha (AG) Unmada such as Jihma Drishtim, Dushtaatmaanaam, Krodhanam, Atruptam, Sasweda Gaatram, Deva, Braahmana, Guru Dveshinam, etc shows similarity with various personality disorders.